Functional characterization of mutations in inherited human cPLA(2) deficiency - Reed, Kathleen (2011)
Group IVA cytosolic phospholipase A(2) (cPLA(2)α) catalyzes the first step in the arachidonic acid cascade leading to the synthesis of important lipid mediators, the prostaglandins and leukotrienes. We previously described a patient deficient in cPLA(2)α activity, which was associated with mutations in both alleles coding for the enzyme. In this paper we describe the biochemical characterization of each of these mutations. Using saturating concentrations of calcium we showed that the R485H mutant was nearly devoid of any catalytic activity, that the S111P mutation did not affect the enzyme activity and that the known polymorphism K651R was associated with slightly higher activity than wild type. Using MDCK cells, we showed that translocation to the Golgi in response to serum activation was impaired for the S111P mutant but not for the other mutants. Using immortalized mouse lung fibroblasts lacking endogenous cPLA(2)α activity, we showed that both mutations S111P and R485H/K651R caused a profound defect in the enzyme catalytic activity in response to cell stimulation with serum. Taken together, our results show that the mutation S111P hampers calcium binding and membrane translocation without affecting the catalytic activity, and that the mutation R485H does not affect membrane translocation but blocks catalytic activity leads to inactivation of the enzyme. Interestingly, our results show that the common polymorphism K651R confers slightly higher activity to the enzyme suggesting a role of this residue in favoring a catalytically active conformation of cPLA(2)α. Our results define how the mutations negatively influence cPLA(2)α function and explain the inability of the proband to release arachidonic acid for eicosanoid production.